2023
DOI: 10.1007/s11356-023-28329-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety accident analysis of power transmission and substation projects based on association rule mining

Abstract: To achieve the sustainable development goals (SDGs) of power transmission and substation project construction, statistical analysis was used to provide an outline of safety accidents, the 4M1E method was applied for sorting out and analyzing the risk factors, and the Apriori algorithm was carried out for exploring the intrinsic interaction among risk factors based on association rule mining. The results showed that the safety accidents that happen in the construction of power transmission and substation projec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Mao, Y. and Tuo, X. suggested that The risk awareness of personnel, the application level of information technology, the way the interests of supply chain stakeholders are distributed, the level of government support, and the regulatory ability of enterprises will affect PBSCR according to the analysis of the critical path. This is similar to the 4M1E theory [55,56]. "4M1E" refers to man, machine, material, method, and environment.…”
Section: Discussionmentioning
confidence: 60%
“…Mao, Y. and Tuo, X. suggested that The risk awareness of personnel, the application level of information technology, the way the interests of supply chain stakeholders are distributed, the level of government support, and the regulatory ability of enterprises will affect PBSCR according to the analysis of the critical path. This is similar to the 4M1E theory [55,56]. "4M1E" refers to man, machine, material, method, and environment.…”
Section: Discussionmentioning
confidence: 60%
“…exhibit a signi cant correlation with safety incidents, highlighting the need to emphasize the role of personal characteristics in safety training and strategy formulation (Castillo-Rosa et al, 2017). While the overall injury rates in the electrical-related industries show a declining trend, speci c high-risk populations still face elevated injury risks, necessitating targeted safety measures (Volberg et al, 2017;Liu et al, 2023). Additionally, personal factors, safety climate, and health conditions signi cantly impact occupational accidents, with age, job roles, education, and experience playing crucial roles in safety behavior (Baby et al, 2021).…”
Section: Electrical Safety Accident Researchmentioning
confidence: 99%
“…Risk identification is the primary task of risk management of PPP projects, which is the process of judging, confirming, and summarizing the potential risk factors faced by the target project. There are many studies on risk identification of PPP projects, both domestically and internationally, covering the risks of various aspects and stages of PPP projects [19,[24][25][26][27]. Lai et al summarized the current status of risk identification, risk assessment, and risk early warning research of PPP infrastructure projects in order to construct a theoretical framework for risk analysis and early warning of PPP projects in characteristic towns, which might benefit future research [28].…”
Section: Risk Identification Of Ppp Projectsmentioning
confidence: 99%